Therapeutic and diagnostic challenges for frontotemporal dementia - D’Alton, Simon; Lewis, Jada (Frontiers in Aging Neuroscience, 2014)
In the search for therapeutic modifiers, frontotemporal dementia (FTD) has traditionally been overshadowed by other conditions such as Alzheimer’s disease. A clinically and pathologically diverse condition, FTD has been galvanized by a number of recent discoveries such as novel genetic variants in familial and sporadic forms of disease and the identification of TAR DNA binding protein of 43kDa (TDP-43) as the defining constituent of inclusions in more than half of cases. In combination with an ever-expanding knowledge of the function and dysfunction of tau - a protein which is pathologically aggregated in the majority of the remaining cases - there exists a greater understanding of FTD than ever before. These advances may indicate potential approaches for the development of hypothetical therapeutics, but FTD remains highly complex and the roles of tau and TDP-43 in neurodegeneration are still wholly unclear. Here the challenges facing potential therapeutic strategies are discussed, which include sufficiently accurate disease diagnosis and sophisticated technology to deliver effective therapies.